Socio-ecological problems: How reflective and impulsive students demonstrate mathematical literacy - Fuadah, Putri Fithrotul; Shodikin, Ali (Universitas Islam Negeri Raden Intan Lampung, 2026)
Mathematical literacy in socio-ecological contexts remains underexplored, particularly when examined in terms of cognitive style. This study aims to describe the mathematical literacy processes of reflective and impulsive junior high school students when solving Minimum Competency Assessment (MCA) tasks that involve socio-ecological issues. A qualitative descriptive design was employed, involving two high-mathematical-ability students selected purposively and classified as reflective and impulsive using the Matching Familiar Figures Test (MFFT). Data were collected through socio-ecological MCA tasks on school waste generation and semi-structured interviews. The data were analyzed using thematic coding based on the PISA mathematical literacy processes (formulate, apply, and interpret). The findings indicate that reflective students demonstrated more systematic verification and deeper contextual interpretation. In contrast, impulsive students applied strategies more rapidly but showed reduced monitoring accuracy, resulting in calculation errors despite appropriate procedural strategies. These findings underscore the importance of considering cognitive processing characteristics in developing socio-ecological MCA tasks and learning strategies to support higher-order mathematical literacy.